DIAGNOSIS OF SOCIAL PHOBIA: LITERATURE REVIEW (Psychology Travelogs, 2024)
The article is devoted to the problem of psychological diagnosis of social phobia. When reviewing scientific works published in Ukrainian scientific publications over the past 14 years, no publications were found devoted to the review of modern methods of psychological diagnosis of social phobias.The purpose of the article is to conduct a review of foreign scientific literature and find out what are the modern methods of diagnosing social phobia.An overview of foreign scientific publications devoted to psychodiagnostic tools for the study of social phobia is presented. It was found that the following tools are currently available for the diagnostic assessment of social phobia: The Fear Questionnaire developed by Marks and Mathews (1979), this questionnaire contains a social phobia subscale that measures avoidance of social situations; The Social Phobia Scale (SPS) and The Social Interaction Anxiety Scale (SIAS) developed by Mattick and Clarke; The Social Phobia and Anxiety Inventory (SPAI) developed by Turner et al. (1989); The Social Phobia Inventory (SPIN) proposed by Connor et al. (2000); cognitive assessment of social anxiety and social phobia (this assessment includes the following measurements as selfstatements, irrational beliefs, attributions, schemata, expectancies, and self-focused attention); behavioral assessment of social anxiety and social phobia, including: behavioral interviews, self-report inventories (the questionnaire measures are inventories of general fear and anxiety, social anxiety, shyness, and social skill and behavior), self-monitoring diaries, behavioral observation of social performance, and an impromptu speech task. The prospects of further research in order to investigate the ways of overcoming social phobia in teenagers are indicated.
Keywords: social anxiety; social phobia; diagnosis of social phobia; diagnostic tools; questionnaires; scales